2012
DOI: 10.1111/j.1365-2923.2012.04257.x
|View full text |Cite
|
Sign up to set email alerts
|

Residency selection: do the perceptions of US programme directors and applicants match?

Abstract: Medical Education 2012: 46: 491–500 Objectives  This study sought to evaluate the practices and perceptions of US residency programme directors (PDs) and residency applicants with reference to the use of social media and Internet resources in the resident doctor selection process. Methods  A survey was distributed via e‐mail (SurveyMonkey®) to 2592 PDs of programmes in 22 specialties accredited by the Accreditation Council for Graduate Medical Education. A separate survey was distributed to all residency candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Among the platforms studied, Facebook 25,28,3032,3437,39 (n = 8, 27.6%), blogs 13,21,22 (n = 3, 10.3%), Twitter 11,14,16 (n = 3, 10.3%), and podcasts 12,20,23 (n = 3, 10.3%) were the four most common. While the focus of each study pertained to residents, 9 studies 13,17,23,25,2830,33,39 (31.0%) included medical students and 9 studies 14,24,26,27,30,31,33,34,38 (31.0%) included faculty members and program directors (PDs). Among the GME residencies, studies on social media most frequently focused on residents of general/sub-specialty surgery 27,28,34,35,37 (n = 5, 17.2%), internal medicine 11,13,14 (n = 3,10.3%) and anesthesia 12,20,23 (n = 3,10.3%); radiology, emergency medicine, pediatrics, family medicine, and dermatology residents were studied, albeit less frequently with respect to social media.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the platforms studied, Facebook 25,28,3032,3437,39 (n = 8, 27.6%), blogs 13,21,22 (n = 3, 10.3%), Twitter 11,14,16 (n = 3, 10.3%), and podcasts 12,20,23 (n = 3, 10.3%) were the four most common. While the focus of each study pertained to residents, 9 studies 13,17,23,25,2830,33,39 (31.0%) included medical students and 9 studies 14,24,26,27,30,31,33,34,38 (31.0%) included faculty members and program directors (PDs). Among the GME residencies, studies on social media most frequently focused on residents of general/sub-specialty surgery 27,28,34,35,37 (n = 5, 17.2%), internal medicine 11,13,14 (n = 3,10.3%) and anesthesia 12,20,23 (n = 3,10.3%); radiology, emergency medicine, pediatrics, family medicine, and dermatology residents were studied, albeit less frequently with respect to social media.…”
Section: Resultsmentioning
confidence: 99%
“…2628 In a study in the Journal of Surgical Education , Go and colleagues surveyed 250 PDs of general surgery and surgery sub-specialty residency programs on their use of social media sites (Facebook, Twitter, MySpace, etc) to screen applicants. 27 They reported that 17% visit social media sites to gain info about applicants, and that upon doing so, 33.3% of those PDs ranked applicants lower after a review of their social media profile/s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, students are often advised to consider their own USMLE scores when deciding which specialties and programs to rank. In one survey, students applying to residency programs universally regarded Step 1 scores as one of the top academic factors considered by residency program directors when evaluating applicants for residency [3]. Their perceptions are well-founded: in the 2014 national survey of residency program directors across all specialties conducted by the NRMP (N = 1793), the USMLE Step 1 / COMLEX (Comprehensive Osteopathic Medical Licensing Examination) Level 1 score was the most commonly cited factor in selecting applicants to interview, with 94% of respondents indicating that they considered Step 1/ COMLEX Level 1 scores when selecting applicants, while 80% indicated that they considered Step 2 CK / COMLEX Level 2 Cognitive Evaluation (CE) scores.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 33% of the surgical programs, and 38.1% of all programs, ranked applicants lower based upon data from social media websites. 6,7,8 In 2013, a meta-analysis analyzed studies done to determine if the various criteria that program directors use to select and rank their candidates had any relationship to how these candidates actually fare in their residencies. 9 The authors performed a literature search of the following medical and educational databases up through September 4, 2012: Excerpt Medica Database (EMBASE); Education Resources Information Center (ERIC); MEDLINE and PubMed for publications in English that met their selection criteria of comparing a measurable selection strategy with a measureable outcome.…”
Section: Introductionmentioning
confidence: 99%